PENGEMBANGAN KOMPETENSI GURU, MANAJEMEN SDM DAN KOLABORASI ORANG TUA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SDN PERIGI 01 TANGERANG SELATAN - Adinda Prasasti; Khaerunisa Adzani; Tiara Yuniar; Muhammad Nazri Fadillah; Dandi Supriatna; Hendrayadi Hendrayadi (STKIP Pesisir Selatan, 2026)
Critical thinking skills are one of the important competencies of the 21st century that need to be developed from the elementary school level. In practice, improving students' critical thinking skills does not only depend on the learning process in the classroom, but is also influenced by teacher competence, school human resource management, and collaboration between parents and the school. This study aims to describe the development of teacher competence, human resource management, and parent collaboration in an effort to improve students' critical thinking skills at SDN Perigi 01 Tangerang Selatan. This study uses a qualitative approach with a case study type. The research subjects included the principal, teachers, students, and parents. Data collection techniques were carried out through interviews, observation, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that teacher competency development is carried out through training, working group discussions, academic supervision, and the development of learning tools that are more oriented towards active learning. Good teacher competence contributes to teachers' ability to implement learning strategies such as discussion, problem solving, inquiry, and providing open-ended questions that encourage students to analyze, argue, and draw conclusions. From a human resource management perspective, schools have implemented the functions of planning, organizing, coaching, and evaluating teachers, although further strengthening of the sustainability of professional development programs and follow-up supervision is still needed.